New Design Valve in Flow Injection System for the Determination of Pb(II) in Biological and Environmental Samples - Thekrayat Joodi Jassim; Raisan Kadhim Taresh (Indonesian Journal of Chemistry, 2023)
A strategy to design an injection valve for a streamlined flow injection technique is described as speed and low-cost materials available in the environment for the determination of Pb(II) ion using the organic reagent 4-((4-methoxyphenyl)diazenyl)benzene-1,3-diol at a wavelength of 498 nm. The scope of the study is to find the optimal conditions, including the flow rate of the carrier, the dispersion coefficient, the length of the reaction coil, and the calibration drawing. The results showed that the optimum length of the reaction coil is 20 cm, and the optimum flow rate is 9.1 mL/min, which is equivalent to the pumping rate of 70 F/min. The range of linearity of the study was revealed by a calibration curve of 0.5–27 mg/L, slope = 1.507, correlation coefficient = 0.9995, the limit of quantitative (LOQ) = 0.088 mg/L, and limit of detection (LOD) = 0.026 mg/L. The system under study has a characteristic efficiency. The dispersion coefficient was calculated for concentrations of 10–15 mg/L Pb(II) ion. Furthermore, the accuracy of the flow injection technique in the estimation process was studied and compared with the Flame Atomic Absorption Spectroscopy (FAAS) technique.